Temporal weighting of binaural cues revealed by detection of dynamic interaural differences in high-rate Gabor click trains - Stecker, G. Christopher (Acoustical Society of America, 2010)
Listeners detected interaural differences of time (ITDs) or level (ILDs) carried by single 4000-Hz Gabor clicks (Gaussian-windowed tone bursts) and trains of 16 such clicks repeating at an interclick interval (ICI) of 2, 5, or 10 ms. In separate conditions, target interaural differences favored the right ear by a constant amount for all clicks (condition RR), attained their peak value at onset and diminished linearly to 0 at offset (condition R0), or grew linearly from 0 at onset to a peak value at offset (condition 0R). Threshold ITDs and ILDs were determined adaptively in separate experiments for each of these conditions and for single clicks. ITD thresholds were found to be lower for 16-click trains than for single clicks at 10-ms ICI, regardless of stimulus condition. At 2-ms ICI, thresholds in RR and R0 conditions were similar to single click thresholds at 2-ms ICI; thresholds in the 0R condition were significantly worse than for single clicks at 2-ms ICI, consistent with strong rate-dependent onset dominance in listeners’ temporal weighting of ITD. ILD thresholds, in contrast, were predominantly unaffected by ICI, suggesting little or no onset dominance for ILD of high-rate stimuli.